(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Power electronics advancements in recent years have had a significant influence on the functioning induction machine drives, as well as speed control My work provides a novel stinger approach for managing the pitch of a thirty motor. The speed of a three-phase inductor may be controlled using either a pm dc motor control technique or directly adding inertia to the stator winding, as per the documentation. My study is focused on developing a modern analogue synth controller system which allows regulating the frequency of a 3 electrical machine with transcending the limits of present methods. In this technique, a quadcopter circuit will be developed and when the helicopter’s load current grows, the multiple impulse tire’s pressure increased as well. On the MATLAB/Simulink framework, the same experiment will be run with turbine load resistance.